Urban economy or environmental policy? The case of Egypt - Zetter, R; Hassan, A (2002)
This paper shows how prevailing economic development paradigms over the last five decades have favoured an urban-based model of economic development at the expense of environmental considerations in developing countries. How the disjuncture between these competing agendas has been experienced in Egypt forms the focus of the paper. Tension between environmental and development/ urbanization policies reflects their political encoding aimed at maintaining regime stability. The state has attempted to mediate between the domestic interests of an urban-based elite and the urban poor, international donor dominance of Egypt's economic and urban development strategies, and the country's limited institutional capacity to manage its developmental aspirations. In a policy configuration that buttresses macro-economic policy with urban development priorities, the unfettered role of market processes has produced vast but unregulated urban expansion with, now, increasingly severe environmental consequences. Despite attempts to reconcile the two agendas in the last decade, the paper concludes that the main issues endemic to the public policy domain in Egypt, and in many developing countries, remain: poor line ministry coordination, weak enforcement of environment law, resistance to participation, limited implementation capacity, conflicts between sectoral and cross-sectoral policy formulation, and dependency on external donors. Copyright © 2002 John Wiley and Sons, Ltd.